A one-pot method for building colloidal nanoparticles into bulk dry powders with nanoscale magnetic, plasmonic and catalytic functionalities. (June 2019) - Ye, Ziwei; Li, Chunchun; Skillen, Nathan; Xu, Yikai; McCabe, Hannah; Kelly, Jessica; Robertson, Peter; Bell, Steven E.J.
Graphical abstract: Highlights: Stable oil-in-water pickering emulsions were prepared using a broad range of aqueous colloidal nanoparticles. Pickering emulsions were transformed in situ into nano-micro-particles consisting of an exposed layer of nanoparticles anchored on a polymer core. Nano-micro-particles carrying a layer of plasmonic nanoparticles are highly SERS active. Nano-micro-particles carrying a layer of TiO2 nanoparticles possess high photocatalytic activity. Abstract: Building easy-to-handle bulk materials with nanoproperties is crucial for many nanotechnology-based real-world applications. Here, we describe a simple one-pot method based on nanoparticle self-assembly of pickering emulsions and in situ polymer deposition for preparing particles consisting of a rigid micro-polymer core covered in exposed surface layers of nanoparticles, which we have named nano-micro-particles (NMPs). Unlike simple colloids, these NMPs can be filtered off from the aqueous suspensions in which they are prepared and dried to form free-flowing powders, which most importantly, retain the properties of the constituent nanoparticles in the surface layer. These NMPs can be stored for extended periods but then used either in the dry state or be re-suspended into liquid media as required. The preparation method is very general and can be readily extended to assemble various types of nanoparticles regardless of their material composition or morphology. In addition, functional components, such as magnetic particles or fluorescent tags, can be encapsulated within the polymer core. This method is a platform technology for building nanoparticles into bulk materials with nano-functionalities tailored toward real-life applications. This is illustrated with examples of the preparation of NMPs suitable for rapid and low-cost on-site water monitoring and remediation.